TOPONIMI DESA DI PULAU BAWEAN, KABUPATEN GRESIK: KAJIAN ETNOLINGUISTIK - Purnama, Melisa Wulan; Hamida, Layli (ETNOLINGUAL, 2024)
The research entitled "Toponymy Village on Bawean Island, Gresik Regency, East Java: Ethnolinguistic Studies" has 2 (two) objectives, namely identifying toponymous forms of village names on Bawean Island, Gresik Regency, East Java; and describing and explaining the ethnolinguistic perspective in the toponym of village names on Bawean Island, Gresik Regency, East Java. This study analyzed the names of 30 villages in Bawean Island using a qualitative descriptive method. The data obtained in this study through the participant as observer technique were then aligned with in-depth interviews with the research subjects. In this study, the researcher found forms of morphological processes, forms of toponymy based on naming theory, and physical characteristics behind the naming of village names on Bawean Island, Gresik Regency, East Java. In this study, it could be found legends, folklore, physical characteristics and the Bawean language as the background for naming village names on Bawean Island. This indicates that culture greatly influences the naming of village names on Bawean Island, Gresik Regency, East Java.